2017
DOI: 10.6007/ijarbss/v7-i7/3153
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Challenges for Professional Development of Malaysian Teachers

Abstract: This paper reviews the strategies and challenges for professional development of Malaysian teachers. In relation to the government's effort to improve teacher professional development, many English as a second language (ESL) teachers register themselves to the 'Teacher's First-Degree Programme' organized by the Ministry of Education. The participants of the programme, somehow, face a number of challenges. The main challenge is the adult ESL teachers need to follow in doing the degree part time as all of them a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In a similar vein Omar, Rashid, Mohamad and Yusof (2017), observed that distance, job commitment and allocation of time, financial problems and family commitment tend to hinder teachers from participating in professional development programmes. In addition, Gomba (2019), posited that lack of interest by the teachers, lack of support by school management by not providing the teachers with requisite incentives and time for professional development, lack of understanding of the value of professional development and poor ICT skills among teachers all contribute to hinder teachers in the rural areas from taking advantage of professional development training.…”
Section: Challenges Of Professional Development Programmesmentioning
confidence: 86%
“…In a similar vein Omar, Rashid, Mohamad and Yusof (2017), observed that distance, job commitment and allocation of time, financial problems and family commitment tend to hinder teachers from participating in professional development programmes. In addition, Gomba (2019), posited that lack of interest by the teachers, lack of support by school management by not providing the teachers with requisite incentives and time for professional development, lack of understanding of the value of professional development and poor ICT skills among teachers all contribute to hinder teachers in the rural areas from taking advantage of professional development training.…”
Section: Challenges Of Professional Development Programmesmentioning
confidence: 86%
“…Yet and Noordin (2017) mentioned how technology has become embedded in the ESL classroom and that pre-service ESL teachers need to be equipped with relevant skills that can allow them to organise and manage assessments more efficiently by using the available technologies. In terms of professional development, although studies like Pang (2017) and Omar, Rashid, Mohamad and Yusof (2017) have stated that ESL teachers take part in continuous in-service training, the rate of learning among teachers when it concerns the use of self-paced assessment is still low. Hence, there needs to be more inclusion of self-paced assessment topics in trainings of in-service and pre-service ESL teachers in Malaysia.…”
Section: Training Of Esl Teachersmentioning
confidence: 99%
“…They further argued that rigid and inflexible teaching timetables and teacher workload were the main constraints that affect individual teacher's attendance in professional development programmes. Among Malaysian teachers, Omar et al (2017) identified complex bureaucratic approval systems, distance, the high cost of fees and workload at school as impediments to pursuing effective CPD. Opfer and Pedder (2011) add that most CPD activities have remained traditional in terms of the short durations assigned to them and the focus has been increasingly aligned with content without recourse to active and self-directed learning as desired by adult learners.…”
Section: Introductionmentioning
confidence: 99%